Breves notas sobre a Geografia da Infância: olhares para percebermos as GeoGrafias da vida - Vitor Rodrigues Oliveira, João; Clara Medeiros de Souza, Ana; Martins de Almeida , Wesley; de Carvalho Alves, Rahyan (Revista Vozes dos Vales: Publicações Acadêmicas, 2024)
This work aims to discuss the importance of the Geography of Childhood, bringing a reflection of the proposed theme, approaching from the Geographic categories space and place, dialoguing with Humanistic Geography. The methodological procedure used was bibliographical research and reworking, based on Piaget (1999; 2013), Tuan (1980; 1982) and Lopes (2006; 2008; 2022). The Geography of Childhood invites us to take a closer look at children’s links with the places where they live and the subjectivity of their perception of them, highlighting its relevance as an urgent and necessary area of research in the field of Geography.